2009
DOI: 10.2166/wst.2009.419
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of attached growth nitrification in cold climates

Abstract: The rate of nitrification within a laboratory-scale Biological Aerated Filtration treatment system at 48C was investigated during an exposure time of approximately four months (acclimatized experiments). In addition, shock experiments from 208C to 48C and from 48C to 208C were performed. The acclimatized experiments demonstrated that the exposure time the system remained at low temperature strongly affects the rates of nitrification. Nevertheless, the experiments showed that significant nitrification rates are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 15 publications
8
36
0
Order By: Relevance
“…The traditional 0 values resulted in high predicted rates and, as such, the Delatolla et al (2009) 9 model was investigated and showed a strong correlation to the measured relative ammonia removal rates throughout various stages of the experiments, where the 9 value changes with exposure time. Furthermore, it should be noted that the Delatolla et al (2009) 9 model showed a stronger correlation relative to rates of removal after an acclimatization period compared to after rapid temperature changes. (10614303) is the property of Water Environment Federation and its content may not be copied or emailed to multiple sites or posted to a listserv without the copyright holder's express written permission.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The traditional 0 values resulted in high predicted rates and, as such, the Delatolla et al (2009) 9 model was investigated and showed a strong correlation to the measured relative ammonia removal rates throughout various stages of the experiments, where the 9 value changes with exposure time. Furthermore, it should be noted that the Delatolla et al (2009) 9 model showed a stronger correlation relative to rates of removal after an acclimatization period compared to after rapid temperature changes. (10614303) is the property of Water Environment Federation and its content may not be copied or emailed to multiple sites or posted to a listserv without the copyright holder's express written permission.…”
Section: Resultsmentioning
confidence: 98%
“…The model provides a relative removal rate predicted for both reactors at 1 °C of approximately 19% and demonstrates a strong correlation to the measured data with time as opposed to the traditional theta model that provides a single removal rate at a given temperature. The R^ values for the Delatolla et al (2009) 9 model following the acclimatization period were 0.86 for Rl and 0.84 for R2, while the R^ values decreased to 0.68 and 0.82 for Rl and 0.63 and 0.41 for R2 during the first and second temperature shock events, respectively (Table 3). Therefore, the Delatolla et al (2009) 9 model performed best affer an acclimatization period compared to shock temperature changes.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations